Urodynamic changes following laparoscopic versus vaginal hysterectomy - Tamer Abouelgreed; Doaa Saleh; Mohamed Abdelaal; Adel Elatreisy; Mohamed Elhelaly; El-Sayed El-Agamy; Ahmed Elgammal; Ashraf Moawad (Archivio Italiano di Urologia e Andrologia, 2022)
Objective: To compare urodynamic changes before and after hysterectomy (laparoscopic vs. vaginal approach) for benign gynecological diseases. Patients and methods: A total of 90 women with a mean age of 56.36-years were enrolled in this study between August 2019 and April 2021. They were divided into two equal groups (45 patients each). Group, I had a vaginal hysterectomy, and Group II had a laparoscopic hysterectomy. All patients were assessed clinically using ICIQ-FLUTS questionnaire and a uro-dynamic study before and six months after surgery. Results: Both vaginal and laparoscopic hysterectomy did not signiﬁcantly change the maximum ﬂow rate, voiding time, and average ﬂow rate. The increase in residual urine volume in group I was not signiﬁcant (p = 0.129), as was in Group II (p = 0.217). All the modiﬁcations, however, were within permis-sible limits. According to the cystometry result, volume at initial sensation rose in both groups after surgery, with no statistically signiﬁcant difference (p = 0.364). After both forms of hysterecto-my, maximum bladder capacity did not vary considerably. Preoperatively, all study participants exhibited no overactivity of the detrusor muscle; nevertheless, following surgery, overac-tivity was noted in 9 patients after vaginal hysterectomy com-pared to three patients after laparoscopic hysterectomy, and all the alterations were within a clinically acceptable range. In addition, the ICIQ-FLUTS score was not signiﬁcantly different between the study groups. Conclusions: According to the urodynamic study, hysterectomy for benign uterine conditions, whether vaginal or laparoscopic did not adversely affect urinary bladder function.